A simple algorithm for differential diagnosis in hemodynamic shock based on left ventricle outflow tract velocity–time integral measurement: a case series - Mercadal, J.; Borrat, X.; Hernández, A.; Denault, A.; Beaubien-Souligny, W.; González-Delgado, D.; Vives, M. (The ultrasound journal, 2022)
Echocardiography has gained wide acceptance among intensive care physicians during the last 15 years. The lack of accredited formation, the long learning curve required and the excessive structural orientation of the present algorithms to evaluate hemodynamically unstable patients hampers its daily use in the intensive care unit. The aim of this article is to show 4 cases where the use of our simple algorithm based on VTI, was crucial. Subsequently, to explain the benefit of using the proposed algorithm with a more functional perspective, as a means for clinical decision-making. A simple algorithm based on left ventricle outflow tract velocity–time integral measurement for a functional hemodynamic monitoring on patients suffering hemodynamic shock or instability is proposed by Spanish Critical Care Ultrasound Network Group. This algorithm considers perfusion and congestion variables. Its simplicity might be useful for guiding physicians in their daily decision-making managing critically ill patients in hemodynamic shock.